«A los vasallos de este yndico continente»: Visita general, población y reformismo borbónico en el partido de Arica, 1793-1796 - Choque Mariño, Carlos (Pontificia Universidad Católica del Perú, 2024)
The implementation of the Bourbon reforms in the viceroyalty of Peru sought to limit the power of the viceroys and the influence of the Peruvian elite on the government, installing for this purpose greater control over the territory from the perspective of the ministers of the Council of the Indies. In this context, the general visit of the mayor Antonio Álvarez y Ximénez to the district of Arica, made between 1793 and 1796, aimed at understanding the state of the province and solving problems linked to the economy, population, justice, security and colonial bureaucracy. The purpose of this article is to describe and analyze part of the implementation of the Bourbon reforms in the Arica district, and its political, economic and social consequences.

La implementación de las reformas borbónicas en el virreinato del Perú buscó limitar el poder de los virreyes y la influencia de la élite peruana en el gobierno, instalando para ello un mayor control sobre el territorio desde la perspectiva de los ministros ilustrados y la Metrópoli. En este contexto, la visita general del intendente Antonio Álvarez y Ximénez al partido de Arica, realizada entre 1793 y 1796, tuvo por finalidad conocer el estado de la provincia y resolver los problemas vinculados a la economía, población, justicia, seguridad y burocracia colonial. El propósito del presente artículo es describir y analizar una parte del proceso de implementación de las reformas borbónicas en el partido de Arica, y sus consecuencias políticas, económicas y sociales.
«To the vassals of this yndic continent»: General visit, population and Bourbon reformism in the District of Arica, 1793-1796
Keywords: Arica; Perú; Indigenous; Mayors; Visits; Bourbon reforms; Arica; Perú; Indígenas; Intendencias; Visitas; Reformas borbónicas; https://purl.org/pe-repo/ocde/ford#6.01.01